The Efforts to Improve Student Learning Outcomes with an Online Material Solution in School Classes in Rural Indonesia - Muhammad Tahajjudi Ghifary; Suryanto; Sri Iswati; Suwarni; Bambang Purwoko (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
This article was an effort to improve student learning in schools in rural areas that can be made by various solutions, including utilizing materials available on the Internet. The authors believe that schools in remote areas did not necessarily have to surrender to their conditions, but they must make various efforts to improve the quality of learning. Therefore, we have carried out this study by utilizing many existing data and literature sources, found by searching the Internet. Next, we examined the phenomenological approach to find an answer from a large number of data at the highest level. The analysis involved coding the data, evaluating, and drawing conclusions that we believe can answer the main problem. Based on the analysis and discussion of the results, we can conclude that the learning problems in remote areas can be solved using the internet network, which has slowly penetrated remote areas. The result was also said that online materials were solution when teachers and resources were limited access, and these online materials barely distinguish between schools in cities and villages. Thus, the results of this study can add insights that were useful at the academic level of high schools and their benefits for policy courts in government and education practitioners in the field. Keywords: Students Learning Outcomes, Online Materials, Rural School